PENGARUH GROWTH OPPORTUNITY, PERTUMBUHAN ASET, PROFITABILITAS, DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PROPERTI DAN REAL ESTATE - Mohammad Arridho Nur Amin; Amirah Amirah; Lukman Abdul Azis (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
The purpose of this study is to determine whether there is an effect of Growth Opportunities on capital structure, to determine the effect of Asset Growth on capital structure, to determine the effect of Profitability on capital structure, to determine the effect of Business Risk on capital structure and to determine the effect of Growth Opportunities, Asset Growth, Profitability, and Business Risk to Capital Structure together with capital structure. The population and sample in this study were 17 property and real estate companies using a purposive sampling method. The data used in this study is secondary data in the form of financial statements of Property and Real Estate Companies Listed on the Indonesia Stock Exchange for 2017-2021. While the data analysis used is multiple linear regression analysis using SPSS version 26. The results of the analysis of this study are Growth Opportunity has an effect on capital structure with a significant level of 0.000 (<0.05). Asset growth has no effect on capital structure with a significant level of 0.501 (> 0.05). Profitability has an effect on capital structure with a significant level of 0.018 (<0.05). Business risk has no effect on capital structure with a significant level of 0.527 (> 0.05) and Growth Opportunity, Asset Growth, Profitability and Business Risk together have an effect on capital structure with a significant level of 0.000 (<0.05).